WATER QUALITY OF LAKE EŁK AS A FACTOR CONNECTED WITH TOURISM, LEISURE AND RECREATION ON AN URBAN AREA - Tandyrak, Renata; Parszuto, Katarzyna; Grochowska, Jolanta (Quaestiones Geographicae, 2016)
Lake Ełk as an important element of the urban landscape is associated with tourism and active recreation and because of it with the economy of the town. Since 1999 the renovation method with the use of artificial aeration with simultaneous phosphorus inactivation and also as a biological filter – BIO HYDRO structures were applied on the lake. This process was lasting 10 years and brought only a short-term improvement. At the same time, the shores of the lake were managed to develop of lake tourism: beach, swimming pool, tennis courts, a promenade, and two a water equipment rentals. The illuminated fountain, the road bridge and well – developed catering – accommodation base were made as well.